CFD-Based Feasibility Study of Laser-Directed Energy Deposition With a Metal Wire for On-Orbit Manufacturing - Noori Rahim Abadi, Seyyed Mohammad Ali; Hagqvist, P.; Sikström, F.; Choquet, I. (Frontiers in Space Technologies, 2022)
Additive manufacturing of parts on site in space requires investigating the feasibility of adapting to zero-gravity and near-vacuum conditions a technology applied today on Earth at standard conditions. While first studies have been conducted for powder bed fusion, feasibility study remains to be explored for direct energy deposition with laser beam and metal wire. This is the purpose of this study, which is conducted using a modelling approach based on computational fluid dynamics. The simulation model developed in that aim includes melting, re-solidification, vaporization, prediction of beam energy absorption as function of the local surface temperature and curvature, ray tracing, tracking of free surface deformation and metal transfer, and wire resistive heating. The study is made by starting from process parameters suited for stable on-Earth metal deposition. These conditions were also studied experimentally to validate the simulation model, leading to satisfactorily results. Three other test cases with ambient pressure lowered down to near-vacuum and/or gravitation down to zero are investigated. It is found that, compared to on-Earth conditions, in-space conditions can induce vaporization of the metal alloy that is large enough to result in a curvature of the melt pool free surface, but too small to lead to the formation of a keyhole. In-space conditions can also modify the force balance at the liquid melt bridge between wire and melt pool, leading to small changes in the curvature and temperature field at the free surface of the wire tip. Among the observed consequences are a small increase of the melt pool length, and a small elevation of the bead height. More importantly for process control, changing to in-space conditions might also affect the stability of the process which could be assessed through the width of the liquid metal bridge. However, by using appropriate process control to maintain a continuous liquid metal bridge, it is concluded that direct energy deposition of metal with laser and wire could be used for manufacturing metal parts in-space at tempered atmosphere.